2016
DOI: 10.1097/mcg.0000000000000519
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Fibrosis Staging of Hepatitis C Patients Using the Electronic Medical Record System

Abstract: Our study demonstrates that HCV-infected patients can be identified and their fibrosis staged using commonly available EMR-based algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[6] We observed that the scores performed better at higher fibrosis stages, with the highest AUROCs observed for the detection of cirrhosis. Given this trend, we hypothesized Figure 1: HCV study population.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…[6] We observed that the scores performed better at higher fibrosis stages, with the highest AUROCs observed for the detection of cirrhosis. Given this trend, we hypothesized Figure 1: HCV study population.…”
Section: Discussionmentioning
confidence: 53%
“…[6] We noticed that the scores were better suited to detect higher fibrosis stages, although their overall performance as judged by AUROCs was only moderate. We hypothesized that an EMR-based approach could be used to identify patients with the most advanced fibrosis stage.…”
Section: Journal Of Translational Internal Medicine / Jan-mar 2017 / mentioning
confidence: 99%
See 1 more Smart Citation